WOMEN AND HOME INDUSTRY: A STUDY ON THE IMPACT OF WOMEN'S EMPOWERMENT IN THE PEANUT CAKE HOME INDUSTRY AS A COMMUNITY EDUCATION STRATEGY - rica adelia rachman; Sri Wahyuni; Ady Setiawan; Arif Sugianto (SOSIOEDUKASI, 2025)
This study aims to analyze the impact of women's empowerment in the home business of making peanut cakes in Balikpapan City. Using a qualitative approach method, it shows the results that this peanut cake home business has a very positive impact on women so that they are empowered in all aspects of life. Through the economic aspect, women can independently generate income and manage finances, socially women can expand their relationships and reach to contribute to the economy, psychological and personal aspects women are more confident and empowered and also have mature thinking in making decisions to be wiser, and finally the educational aspect, the impact in the non-formal education environment, where this effort can be a means for learning sustainable life in the form of community because of the many positive aspects of this business that help people be more skilled in generating income and still get education with a focus on improving skills and financial management.